Numerical evaluation of separation efficiency in the diverging T-junction for slug flow - Ejaz, F. (Emerald Group Holdings Ltd., 2021)
Purpose: Offshore industries encounter severe production downtime due to high liquid carryovers in the T-junction. The diameter ratio and flow regime can significantly affect the excess liquid carryovers. Unfortunately, regular and reduce T-junctions have low separation efficiencies. Ansys as a commercial computational fluid dynamics (CFD) software was used to model and numerically inspect a novel diverging T-junction design. The purpose of diverging T-junction is to merge the specific characteristics of regular and reduced T-junctions, ultimately increasing separation efficiency. The purpose of this study is to numerically compute the separation efficiency for five distinct diverging T-junctions for eight different velocity ratios. The results were compared to regular and converging T-junctions. Design/methodology/approach: Air-water slug flow was simulated with the help of the volume of the fluid model, coupled with the K-epsilon turbulence model to track liquid-gas interfaces. Findings: The results of this study indicated that T-junctions with upstream and downstream diameter ratio combinations of 0.8â1 and 0.5â1 achieved separation efficiency of 96 and 94.5, respectively. These two diverging T-junctions had significantly higher separation efficiencies when compared to regular and converging T-junctions. Results also revealed that over-reduction of upstream and downstream diameter ratios below 0.5 and 1, respectively, lead to declination in separation efficiency. Research limitations/implications: The present study is constrained for air and water as working fluids. Nevertheless, the results apply to other applications as well. Practical implications: The proposed T-junction is intended to reduce excessive liquid carryovers and frequent plant shutdowns. Thus, lowering operational costs and enhancing separation efficiency. Social implications: Higher separation efficiency achieved by using diverging T-junction enabled reduced production downtimes and resulted in lower maintenance costs. Originality/value: A novel T-junction design was proposed in this study with a separation efficiency of higher than 90. High separation efficiency eliminates loss of time during shutdowns and lowers maintenance costs. Furthermore, limitations of this study were also addressed as the lower upstream and downstream diameter ratio does not always enhance separation efficiency. Â© 2021, Emerald Publishing Limited.